An educational experience of cooperative learning in the university - Vergara Rodríguez, Diego (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
An educational experience of cooperative learning approach by means of group work is exposed in this paper. The module involved in this experience (Building and Construction Materials) is taught in the second academic year of civil engineering degree in the Technical College of Ávila (University of Salamanca). A methodology based on three consecutive phases was used: Presentation-Questions-Answers. Both student effort and student motivation were far higher than expected by the professor. The surveys given to the students after the course indicate that the experience was rewarding for them, too.